Understanding and readiness in facing IR 4.0 future skills transformation among UPM trainee counsellors - Balan, Subash; Zainudin, Zaida Nor; Ab. Jalil, Habibah (Canadian Center of Science and Education, 2021)
ndustrial Revolution (IR) 4.0 refers to the integration of technology within a particular industry, which encompasses big data, data analytics, cloud computing, robots, artificial intelligence, as well as Internet of Things (IoT) technologies. This study aims to assess the understanding of trainee counsellors of IR4.0 future skills, and to investigate how trainee counsellors improve their overall understanding of IR4.0 and its readiness. The qualitative research design employed in this study involved semi-structured interviews. Four trainee counsellors were chosen through convenient sampling and interviewed in 15-20 minute sessions. The findings indicate that trainee counsellors have a strong grasp of IR4.0. The respondents acknowledged, however, that their comprehension of IR4.0 in connection with future counselling professions is only modest, owing to the institution’s lack of formal educational exposure. Consequently, the respondents’ readiness to face IR4.0 is dangerously low, with the majority expressing worry towards their adaptability in future career development. Finally, the study concluded that educational institutions are vital in teaching and equipping students to confront the global challenges presented by IR4.0. This study is important because it aids researchers to analyse information on the understanding, readiness, and effect of IR4.0 on future skills among trainee counsellors. Additionally, it helps educational institutions in recognising the essential role of IR4.0 adoption in teaching and learning, as well as the implementation of the necessary measures to increase the readiness for training counsellors in tackling IR4.0.